A combined clinical and biological risk classification improves prediction of outcome in hepatoblastoma patients. (December 2020) - Cairo, Stefano; Armengol, Carolina; Maibach, Rudolf; Häberle, Beate; Becker, Kristina; Carrillo-Reixach, Juan; Guettier, Catherine; Vokuhl, Christian; Schmid, Irene; Buendia, Marie-Annick; Branchereau, Sophie; von Schweinitz, Dietrich; et al.
Abstract: Aim: Stratification of hepatoblastoma (HB) patients is based on clinical and imaging characteristics obtained at the time of diagnosis. We aim to integrate biomarkers into a tool that accurately predicts survival of HB patients. Methods: We retrospectively analysed 174 HB patients for the presence of four biomarkers and explored their prognostic potential by correlating with overall survival (OS) and event-free survival (EFS). Results: Mutations of CTNNB1, NFE2L2  and TERT were found in 135 (78%), 10 (6%) and 10 (6%) patients, respectively, and the adverse C2 subtype of the 16-gene signature in 63 (36%) patients. C2-patients had more frequent metastatic disease, higher alpha-fetoprotein levels, non-fetal histology and significantly worse 3-year OS (68% versus 95%) and EFS (63% versus 87%) than C1-patients. Patients carrying a NFE2L2 mutation had a significantly worse 3-year OS (57% versus 88%) than NFE2L2 wild-type patients and were more likely to have vessel invasive growth and non-fetal histology. TERT mutations were almost exclusively found in older patients, whereas CTNNB1 mutations showed no association with any clinical feature or outcome. In a multivariable analysis, the C2 subtype remained a significant predictor of poor outcome with hazard ratios of 6.202 and 3.611 for OS and EFS, respectively. When added to the Children's Hepatic tumors International Collaboration risk stratification, the presence of the C2 subtype identified a group of high-risk patients with a very poor outcome. Conclusion: We propose a new stratification system based on the combination of clinical factors and the 16-gene signature, which may facilitate a risk-adapted management of HB patients. Highlights: Oncogenic CTNNB1 is the key driver in the genesis of hepatoblastoma. NFE2L2 mutations predict poor outcome and may indicate resistance to chemotherapy. TERT mutations are typical for transitional liver cell tumours in older patients. 16-gene signature enables risk-adapted stratification of hepatoblastoma patients. Biomarkers need to be validated complementary to clinical risk factors in a prospective trial.